Quality Analysis, Phenolic and Flavonoid Content, and Antimicrobial Activity of Stingless Bees Honey (Heterotrigona itama) - Misrahanum Misrahanum; Haya Aqilah; Murniana Murniana (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Stingless bee (Heterotrigona itama) honey has been utilized as a therapeutic ingredient for treating infectious illnesses. This study aims to investigate the quality of stingless honey, total phenolic and flavonoid content, and antimicrobial activity against Staphylococcus aureus, Escherichia coli, and Candida albicans. Honey quality parameters evaluated included organoleptic tests, diastase enzyme activity values, hydroxymethylfurfural (HMF) content, water content, reducing sugar content, honey acidity, and lead (Pb) contamination with test procedures based on the Indonesian National Standard (SNI) 8664: 2018 on honey. The antimicrobial activity test uses the well diffusion method at various concentrations, i.e., 5, 10, 15, 20, and 30%. The results showed four honey quality parameters, i.e., organoleptic, HMF content (0.0054 mg/kg), water content (27.41%), and lead metal contamination levels (0.001198 mg/kg). Honey contained total phenolic content of 6.56 Â± 0.03 mg GAE/g and total flavonoid levels of 5.80 Â± 0.03 mg QE/g. The stingless honey could stop the growth of Staphylococcus aureus and Escherichia coli at the lowest concentration of 5%, with inhibition zone diameters of 14.7 and 9.3 mm diameters. Stingless bee honey did not affect Candida albicans growth.